Novel therapy for COVID-19 does intravenous ozonated-saline affect blood and tissue oxygenation? - Thorp JA; Hollonbeck SA; Viglione DD; Green PC; Hodge JR; Tamburro JA; Tran TN; Glassman DS (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Introduction: Adjunctive ozone therapy for COVID-19 is being used successfully in China, Spain, Italy, and South America. One proposed mechanism is by improving blood / tissue oxygenation thus averting multiorgan system failure due to hypoxia. The purpose of this study was to determine if ozonated-saline administered intravenously affects the oxygenation and duration of time spent in a hypoxia chamber. Materials and methods: This was a prospective pilot study that used one volunteer who underwent seven experiments. Each included two runs in a hypoxia chamber that resulted in symptomatic oxygen desaturation. One subject was used as his own control in the hypoxia chamber before and after infusion of intravenous ozonated-saline in four paired experiments.Another 3 experiments were performed identically except ozone was not administered. The primary outcome was to test the null hypothesis that ozonated-saline infusion does not affect oxygenation. Results: In four experiments, ozone was associated with a significant increase in time the subject could remain in the hypoxia chamber (P< 0.05). In three control experiments without ozone, there was a significant decrease in time in the hypoxia chamber in the second run compared to the first (P <0.001). Compared to the first run there was a 32.4% increase in the proportion of time in the second run (after ozone) compared to the first run (P <0.0001). In contrast, in the three control experiments without ozone, there was significant decrease in proportion of time the subject could remain in the hypoxia chamber with an average decrease of -43.1% (P < 0.0001). Ozone therapy was associated with a significant delay in lowest oxygen desaturation (P <0.05). In contrast, in the three experimental runs without ozone there was a significant reduction in time to reach the nadir of the desaturation curve in the second run compared to that of the first (P < 0.05). Conclusions: Infusion of intravenous ozonated-saline significantly increases the duration of time that a subject can remain in hypoxia and delays the nadir of the oxygen de-saturation curve.